The Evaluation of Fiber Fraction Content of Oil Palm Frond Fermented by Local Bio Activators Rumen Content As Ruminant Feed - Astuti, Tri; Akbar, Syahro Ali; Iszma, Iszma; Basyirun, Fajri (Journal of Animal Nutrition and Production Science, 2024)
This study aims to evaluate the fiber fraction content of oil palm fronds fermented using a local bio activator of rumen content with different incubation times as ruminant feed. The design used in this study was factorial in a 2 x 3 with 3 replications for each treatment. In factor A there was a type of bio activator A1 (Lactic Acid Bacteria) A2 (Crude Enzyme) while in factor B there was an incubation period of 0 days, 7 days, and 14 days. The parameters were the fiber content of oil palm fronds. There were NDF, ADF, Cellulose, and Hemicellulose. The results showed that fermentation based on local bio activators of livestock waste can reduce lignin content so that it will increase nutrient digestibility. The best results were in fermentation with a source of bioactivator in the rumen with an incubation period of 7 days.